Serial Mediation On Technology Readiness And Trust As Moderator On Students’ Continuance Intention To Use Computer-Based Test System - Mohammed, Ibrahim Babangida (2020)
Universities are investing heavily in different educational technologies to catch up with recent advancement. Such investment will only be successful when the students can make good use of it. Nigerian Universities are making an effort towards deploying the computer-based test (CBT) system component of e-learning technologies to complement the conventional paper-based assessment. However, the long-term success of the system solely depends on the students’ continuance intention to use the system. Previous research mostly focuses on the preadoption factors without looking at the post-adoption variables. There is an evident lack of or absence of studies integrating technology readiness index (TRI) 2.0 and expectation confirmation model (ECM) variables in the same framework. The current study aimed at filling this research gap through careful integration of these two models, together with some selected variables to examine the factors determining the students’ continuance intention to use CBT system in Nigerian Universities.